Colombia: Cali and Palmira. Building knowledge basis to understand the food system, players and enabling environment with a city region perspective - Rankin-Cortázar, Sara (UN-Habitat, 2021)
By fostering and coordinating multi-stakeholder platforms such as the Academic Dialogue Platform on Food and Nutritional Safety, the International Centre for Tropical Agriculture (CIAT) aims to generate knowledge and articulate work on the city’s food system by bringing together key actors from the public sector, research groups and academia, NGOs and civil society. The main goal of this platform is to increase capacity and evidence for stakeholders and policymakers to formulate and implement sustainable food system policies with an urban-rural linkages lens. The dialogues initiated by the platform have scaled up to nourish food policies and local food plans among different levels of local governments, and has promoted key actors’ alliances and partnerships. The platform has been a tool for advocating for improved urban-rural food systems and governance, but also for improved policy decision-making among municipalities and across the urban-rural contiuum.